INFLASI DI PROVINSI SULAWESI SELATAN: ANALISIS HUBUNGAN DINAMIS INFLASI KOMODITAS BARANG/JASA - Azwar Azwar (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2016)
This study is aimed at analyzing the interaction and dynamic corellation among inflation of commodity groups of goods and service by observing their pattern of inflation rate in south sulawesi. Using quarterly data from bank Indonesia From 2006 to 2015 lll, This study is conducted to make estimation by applying vector Auto Regression (VAR) with test of impluse response function (IRF) and Variance Decomposition (VD). The result of the study shows that inflation rate commodity groupsnof goods and service in south sulawesi has some interaction and dynamic corelation affecting each other. The change of inflation rate of groups of prapared food, beverages . cigarette and tabacco is dominantly affected by the change within these groups and other groups such as groups of goods ingredient, clothing, transfortation, and monetary service.